Return to Play After Multi-Ligament Knee Injuries in National Football League (NFL) Athletes. Issue 7 (21st July 2017) - Bakshi, Neil K.; Khan, Moin; Finney, Fred Tolbert; Stotts, Jeffrey; Sikka, Robby Singh; Bedi, Asheesh
Objectives: Return to play (RTP) of NFL athletes following isolated ACL tears has been reported in the literature. However, there have been no studies reporting on RTP of NFL athletes following multi-ligament knee injuries. The authors hypothesize that NFL athletes with multi-ligament knee injuries will have lower RTP rates and longer time to RTP compared to athletes with isolated ACL tears, as reported in the literature. We also hypothesize that athletes with ACL and MCL injuries will have higher RTP rates and shorter time to RTP compared to athletes with an ACL tear and a PCL and/or LCL tear(s). Methods: NFL injury surveillance data was reviewed for all multi-ligament knee injuries between 2000 and 2016 with RTP information. Athletes were excluded if RTP was limited due to reasons unrelated to the injury such as suspension, unrelated injury, or personal matters. Extracted data included injury, RTP, time to return to play (months), number of games played, percent of possible games played, and performance. Results: 51 NFL athletes were found to have multi-ligament knee injuries between 2000 and 2016 that met inclusion and exclusion criteria. 47.1% (24/51) of athletes had ACL and MCL tears. 52.9% (27/51) of athletes had ACL and PCL and/or LCL tears. Of the players with ACL and PCL/LCL tears, there were 8 frank knee dislocations. The overall return to play rate following multi-ligament knee injuries was 62.7%. Athletes with ACL/MCL tears had an RTP rate of 70.8%, while the athletes with ACL and PCL/LCL tears had an RTP rate of 55.6% (p=.26). Athletes with frank knee dislocations had a 50% RTP rate. Mean time to RTP for all 51 athletes was 11.9 ± 3.52 months. The mean time to RTP for athletes with ACL/MCL injuries was 10.4±1.6 months compared with 13.7±4.3 for those with combined ACL and PCL/LCL injuries, and for frank dislocations was 20 ±6.1 (p<.001). Athletes with ACL/MCL injuries were more likely to return to prior performance levels 46% vs 18% compared to those with ACL and PCL/LCL injuries (p < .001). Conclusion: This study is the first to provide important prognostic information for NFL players sustaining multi-ligament knee injuries. The RTP rate for athletes with multi-ligament knee injuries is significantly less than the RTP rate for athletes with isolated ACL tears. In addition, athletes with ACL and MCL tears have a higher RTP rate, a significantly shorter time to RTP, and a higher likelihood of returning to prior performance than athletes with combined ACL and PCL/LCL tears.